Isotropic Expansion of the Intraprostatic Gross Tumor Volume of Primary Prostate Cancer Patients Defined in MRI—A Correlation Study With Whole Mount Histopathological Information as Reference - Kramer, Maria; Spohn, Simon K. B.; Kiefer, Selina; Ceci, Lara; Sigle, August; Oerther, Benedict; Schultze-Seemann, Wolfgang; Gratzke, Christian; Bock, Michael; Bamberg, Fabian; Grosu, Anca L.; Benndorf, Matthias; et al. (Frontiers in Oncology, 2020)
Introduction: An accurate delineation of the intraprostatic gross tumor volume (GTV) is of importance for focal treatment in patients with primary prostate cancer (PCa). Multiparametric MRI (mpMRI) is the standard of care for lesion detection but has been shown to underestimate GTV. This study investigated how far the GTV has to be expanded in MRI in order to reach concordance with the histopathological reference and whether this strategy is practicable in clinical routine. Patients and methods: 22 patients with planned prostatectomy and preceded 3 Tesla mpMRI were prospectively examined. After surgery, PCa contours delineated on histopathological slides (GTV-Histo) were superimposed on MRI using ex-vivo imaging as support for co-registration. According to the PI-RADSv2 classification, GTV was manually delineated in MRI (GTV-MRI) by two experts in consensus. For volumetric analysis, we compared GTV-MRI and GTV-Histo. Subsequently, we isotropically enlarged GTV-MRI in 1mm increments within the prostate and also compared those with GTV-Histo regarding the absolute volumes. For evaluating the spatial accuracy, we considered the coverage ratio of GTV-Histo, the Sørensen–Dice coefficient (DSC), as well as the contact with the urethra. Results: In 19 of 22 patients MRI underestimated the intraprostatic tumor volume compared to histopathological reference: median GTV-Histo (4.7 cm3, IQR: 2.5–18.8) was significantly (p<0.001) lager than median GTV-MRI (2.6 cm3, IQR: 1.2–6.9). A median expansion of 1mm (range: 0-4mm) adjusted the initial GTV-MRI to at least the volume of GTV-Histo (GTVexp-MRI). Original GTV-MRI and expansion with 1mm, 2mm, 3mm and 4mm covered in median 39% (IQR: 2-78%), 62% (10-91%), 70% (15-95%), 80% (21-100), 87% (25-100%) of GTV-Histo, respectively. Best DSC (median: 0.54) between GTV-Histo and GTV-MRI was achieved by median expansion of 2 mm. The urethra was covered by initial GTVs-MRI in 8 patients (36%). After applying an expansion with 2mm the urethra was covered in one more patient by GTV-MRI. Conclusion: Using histopathology as reference, we demonstrated that MRI underestimates intraprostatic tumor volume. A 2mm-expansion may improve accurate GTV-delineation while